PENGEMBANGAN KURIKULUM DALAM MENINGKATKAN MUTU PENDIDIKAN - M. Agung Rizky; Tamyis; Endang Ekowati (UNISAN JURNAL, 2024)
Abstract The aim of the research is to analyze curriculum management in an effort to improve the quality of education. The method used is literature research. with the aim of seeing how curriculum management can improve education through improving the quality of human resources and academic quality. Everyone, including administrators of educational institutions at the central, regional and school levels, must support efforts to improve the quality of education. In the era of regional autonomy, education must be decentralized and each region must have its own quality improvement curriculum. This curriculum should be an elaboration or implementation of the educational curriculum determined by the center. This is in accordance with curriculum needs because local governments and schools, even at the lower level, are given the freedom to develop quality improvement programs. Thus, local governments and schools will compete with each other for educational progress in their areas.